Growth in Syria: losses from the war and potential recovery in the aftermath. Issue 2 (3rd July 2021) - Devadas, Sharmila; Elbadawi, Ibrahim; Loayza, Norman V.
ABSTRACT: This paper addresses three questions: (1) what would have been the growth and income trajectory of Syria in the absence of war; (2) given the war, what explains the reduction in economic growth; and (3) what potential growth scenarios for Syria there could be in the aftermath of war. Conflict impact estimates point to negative GDP growth of −12% on average over 2011–2018, with output contracting to about one-third of the 2010 level. In post-conflict simulation scenarios, the growth drivers are affected by the assumed levels of reconstruction assistance, repatriation of refugees, and productivity improvements associated with three political settlement outcomes: a baseline (Sochi-plus) moderate scenario, an optimistic (robust political settlement) scenario, and a pessimistic (de facto balance of power) scenario. Respectively for these scenarios, GDP per capita average growth in the next two decades is projected to be 6.1%, 8.2%, or 3.1%, assuming a final and stable resolution of the conflict.